Prey Stoichiometry Drives Iron Recycling by Zooplankton in the Global Ocean - Richon, Camille; Aumont, Olivier; Tagliabue, Alessandro (Frontiers in Marine Science, 2020)
Zooplankton occupy a key place in the ocean ecosystems as they constitute a link between primary producers and upper trophic levels, with many commercially important fisheries relying on the presence of zooplankton to sustain fish stocks. Moreover, zooplankton have an important role in supporting primary production as they can recycle large amounts of micronutrients such as iron, facilitating its retention in the surface ocean and alleviating iron limitation of phytoplankton. Intuitively, one may consider that a large quantity of prey should ensure a healthy zooplankton ecosystem, but the microbial oceanic food web is characterized by a great variability in both the composition and quality of preys. This variability may lead to mismatches between predator and prey stoichiometry, which can in turn affect the growth efficiency of zooplankton. Here we show that variations in food quality are the main drivers of changes in iron assimilation and recycling by zooplankton. Making use of a state-of-the-art biogeochemical model that explicitly accounts for the impact of multiple drivers on the iron assimilation efficiency, we quantify the relative drivers of iron recycling in different ocean regions and across seasons. Our results can be reconciled within a conceptual framework that links the assimilation efficiency of zooplankton to predator-prey stoichiometric mismatch and zooplankton physiological assumptions. If predator and prey stoichiometries are close, then the micronutrient assimilation by zooplankton is optimal and recycling is low. Any departure from this optimal stoichiometry leads to a decrease in assimilation efficiency and a subsequent increase in micronutrient recycling. This framework can be used to understand the impact of variability in prey food quality on iron recycling from previous experiments and generates clear hypotheses about the relative importance of recycling for other micronutrients such as copper, cobalt, manganese and zinc. Finally, our findings highlight the importance of future changes in prey food quality in driving recycling rates of micronutrients that can amplify or attenuate any climate driven trends in upper ocean nutrient supply.